Aprovechamiento mejorado en bosques de produccion forestal: estudio de caso Los Filos, Rio San Juan, Nicaragua - Sabogal, C.; Castillo, A.; Carrera, F.; Castañeda, A. (Centro Agronómico Tropical de Investigación y Enseñanza, 2001)
This document describes and analyzes the operations of a technically planned timber harvest applied on experimental scale by a lumber company in a humid tropical forest of the Southeast of Nicaragua. It involves an operational inventory, the planning and building of the network trails and mountain yards, the controlled logging and its dragging and post-harvest activities. The yields and costs were determined for each one of the operations. The costs are similar to those in other regions of the humid tropic. The short term impact of the logging was evaluated in term of the damages to the forest, as well as changes in the silvicultural conditions of the remnants mass. The results show that the damages were smaller, in comparison with traditional methods in Central America; thus, the forest was in good condition to allow its handling in natural form. The population of trees and the regeneration in terms of growth, mortality and recruitment were monitored during four years through a network of permanent plots installed before the intervention. The experience in Rio San Juan indicates that benefits can be obtained with the application of low impact techniques in the commercial timber harvest. One recommendation is to validate these results on an operational scale and increase the information coverage of the results, in order to convince the lumber company, the concessionaire or the forest that a good planning, supervision and qualification in the harvest of the forest is not more expensive and it is at their reach.